Tanggung Jawab Pemerintah Kota Banda Aceh Terhadap Kelancaran Lalu Lintas Jalan Raya - Tommy (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2017)
Government Regulation Number 32 Year 2011 on Management and Engineering, Impact Analysis, And Needs Traffic Management ordered the region to make local regulations related commands, prohibitions, warnings and/or instructions that are common across all the roadway of the city. Until now, none of the local regulations in region about rumble strip as well as the government's responsibility for the impact of losses incurred from the rumble strip. The purpose of this study find alternative solutions to the problems encountered. Based on the object of the problem studied, the research method used is empirical juridical. The effective of rumble strip to raise legal awareness in traffic on a highway Banda Aceh was not followed by the responsibility of municipal authorities to deliver local regulations in determining the locations and conditions of laying rumble strip, the effects and damages arising from the existence rumble strip that so many in the roadway. It is suggested to the Government of Banda Aceh to deliver local regulations pertaining to the rumble strip and curb its existence is so disturbing people in maintaining the smoothness of traffic.